(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study investigated the effectiveness of different physical forms of feed containing Ipomoea aquatica waste and concentrate feed on the rumen characteristics, chewing activity, and performance of sheep. Materials and Methods: Twenty-four rams (19.87 ± 2.19 kg) were arranged in a completely randomized design. Rams were fed dried I. aquatica waste and concentrate feed provided separately (RCF) (conventional feeding system), and total mixed ration consisted of mash complete feed (MCF), and pelleted complete feed (PCF). The data were analyzed using a one-way analysis of variance. Results: The dry matter intake (DMI), average daily gain, and feed conversion ratio of rams fed different physical forms of feed containing I. aquatica waste in their diet were similar between the treatments, ranging from 4.08% to 4.29% of body weight, 120–180 gm, and 6.32–9.17, respectively. Different physical feeds did not affect microbial synthesis in the rumen. Methane emissions per unit of production were similar between the groups. The PCF sheep ate faster (0.24 min/gm DMI) than the MCF sheep (0.38 min/gm DMI), but similar to the RCF sheep (0.31 min/gm DMI). Conclusion: Dried I. aquatica waste was useful as an alternative lamb feed roughage during the dry season. The pelleted mixed ration was more efficient than mash in increasing DMI. The dried I. aquatica waste was environmentally friendly for mitigating enteric methane emissions by sheep. J. Adv. Vet. Anim. Res., 10(4): 677–684, December 2023 http://doi.org/10.5455/javar.2023.j723